Dengeki Daisy. Vol. 5 - Motomi, Kyousuke (Shojo beat manga., 2011)
"While trying to uncover who the fake DAISY is, Kurosaki gets injured protecting Teru from an attack! The near-fatal incident leaves Teru shaken, and she vows to stay close to Kurosaki. But is proximity just going to hurt them both with the truth still veiled?"--P. [4] of cover.